2019
DOI: 10.1155/2019/5828931
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis of Diagnostic Performance of Instantaneous Wave-Free Ratio versus Quantitative Flow Ratio for Detecting the Functional Significance of Coronary Stenosis

Abstract: Background. Fractional flow reserve (FFR), as a functional measurement of coronary stenosis, is recommended for guiding revascularization in intermediate coronary lesions. However, it still remains underutilized for potential reasons including time consumption, costs, or contraindications associated with adenosine administration. Here we performed this meta-analysis to assess the diagnostic performance of two adenosine-free indices, instantaneous wave free-ratio (iFR), and quantitative flow ratio (QFR) in eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…ree previous meta-analyses assessed the diagnostic parameters of QFR for detecting significant coronary stenosis. e reliability of the analysis may have been affected by the lack of current studies and the inclusion of a conference abstract [7,11,12]. Another meta-analysis included 4 well-designed multicenter prospective studies, in which the QFR calculation followed a strict procedure and finished by well-trained operators, but the study sample was relatively small.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…ree previous meta-analyses assessed the diagnostic parameters of QFR for detecting significant coronary stenosis. e reliability of the analysis may have been affected by the lack of current studies and the inclusion of a conference abstract [7,11,12]. Another meta-analysis included 4 well-designed multicenter prospective studies, in which the QFR calculation followed a strict procedure and finished by well-trained operators, but the study sample was relatively small.…”
Section: Discussionmentioning
confidence: 99%
“…By reviewing the current meta-analysis of cFFR and QFR, we found that heterogeneity of the correlation values of cFFR (I 2 � 81.00%) [6] and sensitivity and specificity of QFR (I 2 ranged from 70.1% to 72.07% and 24.1% to 60.1%, resp.) [7,12] both are high. However, despite the large heterogeneity, we found that our research reported consistent results with previous studies, which reported that the sensitivity and specificity of cFFR were 88% and 93%, while the reported sensitivity of QFR ranged from 84% to 89%, with the specificity being 88% [6,7,12].…”
Section: Combinedmentioning
confidence: 97%
See 3 more Smart Citations